ANALISIS BUKU AJAR BAHASA ARAB DALAM PERSPEKTIF THU’AIMAH SEBAGAI UPAYA MENDUKUNG SDGS 4 - Zahra, Salsabila; Tatang; Nurmala, Mia (Al-Ma‘rifah, 2025)
The 2030 Sustainable Development Goals (SDGs), particularly sub-target 4.6, aim to enhance literacy and numeracy skills among adolescents and adults by the year 2030. This study analyzes the mahārat al-kitābah content in the Grade 2 Arabic textbook for Madrasah Ibtidaiyah (MI), published by the Ministry of Religious Affairs in 2020, from the perspective of Rushdī Aḥmad Ṭu‘aymah, and examines its role in supporting the SDGs. Using a qualitative method with content analysis as the primary data collection technique, the study finds that the textbook aligns with Ṭu‘aymah’s framework for teaching mahārat al-kitābah. The content includes recognizing the shapes of hijā’iyah letters, copying letters and words, writing simple sentences, and answering questions in written form. Overall, the mahārat al-kitābah content in the textbook supports foundational Arabic writing skills and contributes to the achievement of SDG 4 by promoting multilingual literacy, equitable access to literacy development, comprehensive language competence, and quality education.